Respuesta :
Let x=the first number
Then x+7=second number
And 4(x+7)+2=third number (2 more than 4 times the second)
Now we are told that:
x+(x+7)+(4(x+7)+2)=85 get rid of parentheses
x+x+7+4x+28+2=85 simplify
6x+37=85 subtract 37 from each side
6x+37-37=85-37
6x=48
x=8---first number
x+7=8+7=15 second number
4(x+7)+2=4*15+2=62 third number
CK
8+15+62=85
85=85
Then x+7=second number
And 4(x+7)+2=third number (2 more than 4 times the second)
Now we are told that:
x+(x+7)+(4(x+7)+2)=85 get rid of parentheses
x+x+7+4x+28+2=85 simplify
6x+37=85 subtract 37 from each side
6x+37-37=85-37
6x=48
x=8---first number
x+7=8+7=15 second number
4(x+7)+2=4*15+2=62 third number
CK
8+15+62=85
85=85
"The sum of three numbers is 85"
x+y+z = 85
"The second number is 7 more than the first."
y = x+7
"The third is 2 more than four times the second."
z = 4y+2
z = 4(x+7) + 2 = 4x+30
x + (x+7) + (4x+30) = 85
6x = 48
x = 8
y = x+7 = 15
z = 4x+30 = 62
Hope this helps!